Tindak Tutur Larangan dan Strategi Kesantunan pada Rambu Kereta LRT–Bahasa Inggris: Analisis Pragmatis - Handayani, Wuriy; Arfani, Sri (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2026)
This study investigates prohibitive speech acts and politeness strategies in Indonesian–English bilingual signage used in the LRT Jabodebek system from a pragmatic perspective. Prohibition signs in public transportation function not only as informational messages but also as regulatory tools that shape passenger behavior in order to maintain safety, order, and comfort. Adopting a qualitative descriptive-analytical approach, the data consist of written prohibition signs collected from stations, train carriages, and supporting facilities through documentation techniques. The analysis is based on Speech Act Theory (Austin, 1962; Searle, 1975), the concepts of directness and indirectness (Blum-Kulka, House, & Kasper, 1989), and Brown and Levinson’s (1987) politeness theory. The findings show that prohibitive speech acts are realized through various linguistic forms, ranging from highly direct imperatives to more impersonal declarative constructions. Safety-related prohibitions tend to employ stronger illocutionary force, whereas comfort-related prohibitions incorporate politeness strategies as a form of mitigation. The use of bilingual signage also enhances clarity and accessibility for diverse passengers, supporting more effective public communication in multilingual transportation settings.